2018
DOI: 10.1038/s41598-018-26111-2
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Process of the Growing Motile Ciliary Tip Region

Abstract: Eukaryotic motile cilia/flagella play vital roles in various physiological processes in mammals and some protists. Defects in cilia formation underlie multiple human disorders, known as ciliopathies. The detailed processes of cilia growth and development are still far from clear despite extensive studies. In this study, we characterized the process of cilium formation (ciliogenesis) by investigating the newly developed motile cilia of deciliated protists using complementary techniques in electron microscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 51 publications
1
22
0
Order By: Relevance
“…The latter two forms are unique to cilia and flagella. Although microtubule doublets were found to become singlets at the tip end of cilia or flagella (29,41,42), the doublet-singlet transitions remain structurally uncharacterized.In this work we determined complete 3D structural maps of epithelial primary cilia using serial section electron tomography (SSET) and developed a 3D structural model of typical primary cilia as an updated structural baseline for primary cilium research. We found that key features of primary cilia architecture are distinct from expectations based on the 9+0 paradigm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The latter two forms are unique to cilia and flagella. Although microtubule doublets were found to become singlets at the tip end of cilia or flagella (29,41,42), the doublet-singlet transitions remain structurally uncharacterized.In this work we determined complete 3D structural maps of epithelial primary cilia using serial section electron tomography (SSET) and developed a 3D structural model of typical primary cilia as an updated structural baseline for primary cilium research. We found that key features of primary cilia architecture are distinct from expectations based on the 9+0 paradigm.…”
mentioning
confidence: 99%
“…The latter two forms are unique to cilia and flagella. Although microtubule doublets were found to become singlets at the tip end of cilia or flagella (29,41,42), the doublet-singlet transitions remain structurally uncharacterized.…”
mentioning
confidence: 99%
“…There is an ultrastructural heterogeneity between the distal tips of different organisms . In the flagellar tips of model organisms like Chlamydomonas reinhardtii or Tetrahymena thermophila , the incomplete B‐tubules of dMTs end and the A‐tubules extend together with the CP to the tip extremity, creating the singlet region . However, this region is completely absent in other models like Leishmania mexicana and Trypanosoma brucei .…”
mentioning
confidence: 99%
“…We sorted the reported flagella tip structures into six different models ( Figure 3). thermophila with three different EM techniques (18,25,26), except that its central pair microtubules extend approximately 200 nm longer than the A-tubules in the singlet region, giving the tip a more protruding shape. The bead of the central microtubule cap was not visible in the cryo-ET reconstructions of T. thermophila flagella tips (26).…”
Section: Structural Models For Distal Tips Of Motile Flagellamentioning
confidence: 99%
“…thermophila with three different EM techniques (18,25,26), except that its central pair microtubules extend approximately 200 nm longer than the A-tubules in the singlet region, giving the tip a more protruding shape. The bead of the central microtubule cap was not visible in the cryo-ET reconstructions of T. thermophila flagella tips (26). Two other species of protist ciliates shared a similar tip ultrastructure (27,28).…”
Section: Structural Models For Distal Tips Of Motile Flagellamentioning
confidence: 99%